PEMANFAATAN POTENSI GEOTERMAL WKP TULEHU MELALUI PEMBANGKIT SIKLUS BINER - Pellu, Deny Ismail; Hatuwe, Azmain Noor (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Geothermal is a new renewable energy model that comes from the bowels of the earth which is exploited using a Geothermal Power Plant (PLTP) into electrical energy. For high-temperature hot steam, it is used directly as a turbine rotation to produce electricity. The Tulehu WKP which has been explored by drilling 5 wells only produces medium-temperature fluids and is estimated to produce around 7 megawatts (MW) of electricity. One method used to increase the efficiency of PLTP is the binary cycle. The binary cycle is a geothermal fluid power generation system that is used to heat the working fluid using a heat exchanger from the liquid phase to the vapor phase which is then used to drive the turbine. Furthermore, the turbine drives the generator and is converted into electrical energy. This study aims to determine the performance of the Organic Rankine Cycle ORC using isopentane, isobutene and butane working fluids to obtain optimal performance. The method used is to use simulation with the Aspen HYSYS application to obtain good and optimal Organic Rankine Cycle (ORC) fluids. From these problems, the Tulehu Geothermal Power Plant can be built using a binary cycle, so in this study an energy analysis was carried out with the Tulehu Geothermal Power Plant binary cycle in order to produce maximum energy. By applying the binary cycle, the power generated reaches 10 MW. Keywords: Geothermal, Binary Cycle, Energy